THE CONDITIONS FOR A SUCCESSFUL DIGITAL TRANSFORMATION FOR A SUCCESSFUL AUDIT FIRM - EL ADIB , Mohamed; NAFZAOUI , Mohamed Achraf (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The digital transformation in the current context is a necessity to survive more than used to seize opportunities. Thus regardless to the type or kind of the organization and regardless to its field of activity, digitalization has just become indispensable and necessary to survive. Indeed, in an environment that is becoming more and more digitalized, audit firms must implement this digital transformation. However, for an efficient and successful implementation, specific and general conditions are required. Indeed, an organizational culture that promotes digital, an effective organizational change, a specific set of resources and competencies and organizational agility are sine qua non conditions for a successful digital transformation. In addition, other conditions are essential for any project implementation, such as team commitment and follow-up, collaboration between different stakeholders, effective internal communication and enriching employee training. For a successful digital transformation all these conditions are essential and constitute a basic pillar for its implementation in order to guarantee a successful and an effective audit firm.